Menganalisis Kesalahan yang Muncul dalam Menghubungkan Filsafat dan Teologi Serta Solusinya - Darius Kahabi Raumbani; Alfin Susanto Zagoto; Mozes Lawalata (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Of the many problems that arise in Christian circles, philosophy and theology are often the subject of serious discussion among theologians. It's not just theologians who debate this, but lay people also debate it. Because if we talk about philosophy and theology, it is clear that there are pros and there are also cons. Philosophy and Theology are two very important sciences that must be studied in human life. There are those who ignore one of the two and there are also those who accept both as good knowledge that will bring a change in human life. The problem in human life is the assumption that the two contradict each other. But the question is; Is it true that philosophy and theology contradict each other? and if it is true that the two contradict each other, is it necessary to ignore one of the two? Everyone has the right to study or not study one of the two. However, the problem is if you make a statement that the two contradict each other but there is no data to support what you say, that is the problem. It is important to know that all sciences have their own advantages, so by knowing that it is clear that there is no reason to make unfavorable statements that turn off other people's interest in studying both. This article focuses on discussing issues surrounding philosophy and theology in Christian circles using data analysis. With the existing data, we will discuss the reasons why people are not interested in studying philosophy. The author's hope is to change the mindset of people who always make statements that philosophy and theology contradict each other. So the fundamental hope of the author is to have openness in all knowledge without any neglect by saying that it is not good in my life as a Christian.